In Vivo Bioluminescence Imaging of Transplanted Mesenchymal Stem Cells as a Potential Source for Pancreatic Regeneration - Song Lee; Hyewon Youn; Taemoon Chung; Do Won Hwang; So Won Oh; Keon Wook Kang; June-Key Chung; Dong Soo Lee (Molecular Imaging)
Stem cell therapy has been studied intensively as a promising therapeutic strategy toward a cure for diabetes. To study the effect of mesenchymal stem cell (MSC) transplantation for pancreatic regeneration, we monitored the localization and distribution of transplanted MSCs by bioluminescence imaging in a mouse model. Bone marrow MSCs were isolated and transfected with a highly sensitive firefly luciferase reporter gene. To assess the efficiency of MSC transplantation, a partially pancreatectomized (PPx) mouse model was used. Transplanted MSCs were monitored by confocal microscopy and in vivo bioluminescence imaging. Daily blood glucose levels and glucose tolerance were measured. Insulin-secreting beta cells were immunostained, and insulin levels were measured via enzyme-linked immunosorbent assay. Bioluminescence signals were clearly detected from the transplanted MSCs in the pancreatic region regardless of injection route. However, locally injected MSCs exhibited more rapid proliferation than ductally injected MSCs. PPx mice harboring transplanted MSCs gradually recovered from impaired glucose tolerance. Although insulin secretion was not observed in MSCs, transplanted MSCs facilitate the injured pancreas to recover its function. In vivo optical imaging of transplanted MSCs using a highly sensitive luciferase reporter enables the assessment of MSC transplantation efficiency in a PPx mouse model.